Spatial speed-accuracy trade-off in international badminton players performing the forehand smash - Afzal, I. A.; McErlain-Naylor, S. A.; Hiley, M.; King, M. (ISBS Proceedings Archive (Michigan), 2020)
Speed and accuracy of the badminton smash are critical components for successful performance. Fifty-two participants data were collected using a Vicon 3D Motion capture system (400 Hz) at the BWF Glasgow World Championships (2017). The purpose of this study was to identify and compare spatial speed-accuracy trade-off (SATO) relationships amongst international badminton players performing the forehand smash, under two conditions: maximal speed (MS) in the direction of a target; and maximal speed aiming to hit the centre of a target (TAR). Exploratory and confirmatory cluster analyses revealed three groupings: Fitts` inverse relationship (FIR), no relationship (NR) and alternate inverse relationship (AIR). Findings indicate that for international badminton players 80-99% of maximum speed is the threshold for achieving the highest levels of spatial accuracy.